Sistem Penjadwalan Kegiatan Fisik Dana Nagari dengan Metode Fuzzy Logic Application for Schedulling - Dona Kurnia; Wizra Aulia (Prosiding SISFOTEK, 2019)
The system of scheduling the physical activities of Nagari Ladang Laweh fund is the scheduling of activities carried out to build the infrastructure of the nagari in the form of Roads, Ditches, Bridges, Houses and other house renovations. During this time the project scheduling of the nagari fund physical activities is based on the analysis of the project implementer and the head of the project so there is no certainty on the duration of the project activities. In this study a measurable method is used in determining the scheduling of physical activities, namely the Flash (Fuzzy Logic Application For Schedulling) method where the Flash method can measure the duration needed for an activity that is able to accommodate uncertainty. The application of this flash method will be supported by an application program that will facilitate the Activity Implementing Team (PK) in determining the duration of an activity carried out. The use of application programs for the decision making process can be done well. From the results of a study of 1 (one) cor jalan Parik Lintang cast activity can be completed in the fastest duration of 58 days, the normal duration of 75 days and the longest duration of 170 days.